THU0642-HPR EVOLUTION OF THE PERCEPTIONS OF RA PATIENTS AFTER EDUCATION PATIENT SESSION TEACHING METHOTREXATE SELF-INJECTION A PROSPECTIVE PILOT STUDY. (2nd June 2020) - Afilal, S.; Rkain, H.; Berchane, B.; Moulay Berkchi, J.; Fellous, S.; Fatima Zahrae, T.; Ilham, A.; Alami, N.; Latifa, T.; Hajjaj-Hassouni, N.; Allali, F.
Abstract : Background: Methotrexate is a gold standard for treatment of RA. In our context, RA patients prefer to be injected by paramedics rather than self-injecting. This can be explained by patients' bad perceptions of self-injection or lack of information. Appropriate self-injection education can therefore be an important element in overcoming these obstacles and improving disease self-management. Objectives: Compare the RA patients' perceptions on methotrexate self-injection before and after a patient education session. Methods: Prospective pilot study that included 27 consecutive patients (81.5% female, mean age 44.4 years, illiteracy rate 40.7%) with RA (median duration of progression of 4 years, mean delay in referral for specialist of 6 months, median duration of methotrexate use of 1 year). The patients benefited from an individual patient education session to learn how to self-inject with methotrexate subcutaneously. The patient education session was supervised by a nurse and a rheumatologist with a control a week later. Perceptions of the reluctance to self-inject and the difficulties encountered by patients were assessed before the patient education session, after the 1st and 2nd self-injection of methotrexate using a 10 mm visual analog scale. Patients also reported their level of satisfaction (10 mm VAS) after the 1st and 2nd self-injection. Results: The mean duration of patient education session is 13 min. Table I compares the evolution of the degrees of reluctance to self-injection, the difficulties encountered, and the satisfaction experienced by the patients. Conclusion: This study suggests the effectiveness of a methotrexate self-injection patient education session in RA patients. It also highlights the value of patient education in rheumatologic care. A large-scale study is necessary to better interpret and complete these preliminary results from this pilot study. Disclosure of Interests: None declared